Investigation of indium oxide as a self-catalyst in ZnO/ZnInO heterostructure nanowires growth - Yousefi, R.; Muhamad, M.R.; Zak, A.K. (Elsevier, 2010)
We investigated the self-catalytic role of indium oxide in the growth process of ZnO/ZnInO heterostructure nanowires on Si(111) The prepared nanowires had hexagonal cross sections and were tapered with tip diameters of 90 +/- 5 nm and base diameters of 230 +/- 5 nm Energy dispersive X-ray and field emission Auger spectroscopes indicated that the grown nanowires were heterostructures of ZnO and ZnInO. Analysis of the early growth process revealed that indium may play a self-catalytic role Therefore, the vapor-liquid-solid mechanism is likely to be responsible for growth of ZnO/ZnInO nanowires. X-ray diffraction and room temperature photoluminescence (PL) data demonstrated that the presence of indium results in a decrease in nanowires' crystallinity These wires produced a large PL emission peak in the ultraviolet (UV) region and a smaller peak in the green region of the electromagnetic spectrum The UV peak of the ZnO/ZnInO nanowires is blue-shifted with respect to that of pure ZnO nanowires (C) 2010 Elsevier B V All rights reserved.